Euphemism of Taboo Language in the Pandhalungan Community in Sukorambi District, Jember - Naily Inayatul Maghfirah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Humans as social creatures cannot be separated from their interactions with each other. In interacting, humans use language as a communication tool. Language is a very important element in human life. The function of language as a communication tool is realized in the process of interaction between humans in social life.  Language development is very dynamic.  Therefore, new languages ​​and new terms related to language may emerge. An example is the emergence of taboo languages. Taboo language is a group of words that are very sensitive to certain groups so that their use or pronunciation is avoided. Saying these taboo words can provoke other people's anger. Languages ​​emerge from specific cultural areas. Jember is one of the areas where Pandhalungan culture is believed to exist. This research was conducted with the aim of analyzing the form of Tabu language used by the Pandhalungan community in the Sukorambi sub-district area, Jember. Apart from that, this research also analyzes the form of euphemization carried out by the Pandhalungan community in the Sukorambi sub-district area, Jember. Based on the data collected, the forms of taboo language used by the Pandhalungan people include the names of certain animals, supernatural creatures, physical disorders and mental disorders. The form of euphemization carried out is changing the way of pronunciation and changing taboo words to other acceptable words